2016
DOI: 10.3856/vol44-issue4-fulltext-14
|View full text |Cite
|
Sign up to set email alerts
|

Composicion de la ictiofauna capturada en la pesqueria artesanal de la Isla Isabel (sureste del Golfo de California), Mexico

Abstract: RESUMEN.La Isla Isabel es un Parque Nacional localizado en el noroeste de México, cuya área marina no está protegida y la pesca artesanal está permitida, aunque los impactos de esta actividad sobre el ecosistema y los recursos naturales explotados no han sido evaluados. De mayo 2013 a abril 2014 se monitoreó mensualmente diferentes campos pesqueros de la Isla Isabel. Los artes de pesca más utilizados fueron la red de enmalle (96,4%), la línea de mano (2,1%) y la cimbra (1,5%), capturándose 2.388 ejemplares per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
0
3
0
2
Order By: Relevance
“…In this study, 2 to 4" mesh sizes were used. Furthermore, unlike the study area reported by Torrescano-Castro et al (2016), which is 35 km away from the nearest coast, the other two studies were conducted in the estuary and adjacent coastal areas, which have a high fishing pressure in both Nayarit and Guatemala (Ramírez-Zavala and Bojórquez-Sauceda, 2006;Ortiz et al 2021). Another factor to consider in the size difference could be the fact that, according to information from the NOAA Weather Forecast Center (NOAA, 2022), the study was conducted in a representative year, whereas that of Ortiz et al (2021) was conducted in the midst of La Niña.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…In this study, 2 to 4" mesh sizes were used. Furthermore, unlike the study area reported by Torrescano-Castro et al (2016), which is 35 km away from the nearest coast, the other two studies were conducted in the estuary and adjacent coastal areas, which have a high fishing pressure in both Nayarit and Guatemala (Ramírez-Zavala and Bojórquez-Sauceda, 2006;Ortiz et al 2021). Another factor to consider in the size difference could be the fact that, according to information from the NOAA Weather Forecast Center (NOAA, 2022), the study was conducted in a representative year, whereas that of Ortiz et al (2021) was conducted in the midst of La Niña.…”
Section: Discussionmentioning
confidence: 91%
“…artisanal fishery of Isla Isabel, Nayarit, Mexico (Torrescano-Castro et al, 2016), larger individuals of C. reticulatus were found (Ẋ = 40.8 cm and = 619.4 g). The difference between the sizes stated in the aforementioned work and the other two can be attributed to the different fishing gear used, since this work reports the use of gill nets with mesh sizes of 8.9, 10.2 and 12.7 cm (3.5, 4 and 5") (for 96.4 % of the total catch), while Ortiz et al (2021) report the use of gill nets with mesh sizes of 5.1 and 7.6 cm (2 and 3").…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…snyderi ) were observed in high abundance in Guatemala and may rank equal to or higher than elasmobranch catches in their importance to the livelihoods of small‐scale fishers and market vendors and as inexpensive sources of essential food to local households. Finally, many of the bony fish species recorded also form important components of the SSF landings described for the Pacific coast of Mexico (Madrid, Sanchez & Ruiz, 1997; Rojo‐Vazquez et al, 2008; Torrescano‐Castro et al, 2016). Given the similar coastal ecology and geographic extent of these species, they may constitute shared stocks and an opportunity to harmonize regulations and management approaches.…”
Section: Discussionmentioning
confidence: 99%